LOCUS OF CONTROL, INNOVATION, PERFORMANCE OF THE BUSINESS PEOPLE IN THE SMALL BUSINESS AND MEDIUM INDUSTRIES IN SOUTH SULAWESI - Muh. Rum (Universitas Hayam Wuruk Perbanas, 2012)
Locus of control has been seen as an important factor in boosting the business performance.Beside, it can also be used as the trigger to enhance the business survival. However, so far,there has no any study especially analyzing this factor in a specific situation such as in Smalland Medium Enterprises (SMEs). The research aims tries to analyze the influence of Locus ofControl, innovation ability on the performance of small medium industry in south Sulawesi.Practically, this research was conducted using survey with purposive sampling on industrialSmall and Medium Enterprises (SMEs) in South Sulawesi, then conducting a clustering onfour regions in northern, southern, eastern, and western areas which were centralized inMakassar municipality. The data were collected by interview and questionnaire to 200 industrialSME owners. Technical analysis data run by use of Structural Equation Model (SEM).The result in, points out that by reinforcing potential Locus of Control can stimulate the increasingof Innovation, and increases the performance of SMEs industry. The reinforcementof Locus of Control can be conducted by increasing memory ability, innovation ability, andPerformance, in terms of employee productivity, ability, and skill.